Lucid nightmares and lucid nightmare distress: associated factors and coping strategies - Löhner, Katharina; Schredl, Michael; Göritz, Anja (Dreaming, 2025)
In lucid dreams, the dreamer knows that they are dreaming and they can be able to control the dream action, which can be used, for example, engaging in fun activities. However, lucid dreams can also manifest as lucid nightmares if, for instance, the dream events cannot be controlled and take a negative turn. As the research landscape on lucid nightmares is sparse, the present cross-sectional online study (N = 1,267) aimed to investigate the predictors of their occurrence as well as the predictors of lucid nightmare distress and strategies people use for coping. The results showed that the participants considered about 21% of their lucid dreams to be lucid nightmares. Ordinal regression analyses revealed that higher neuroticism, more nightmares, and higher lucid dream frequency were associated with more lucid nightmares. More lucid nightmare distress was also connected to higher neuroticism and more nightmares and further to more lucid nightmares as well as with being female. Overall, around 14% of participants with lucid nightmares reported actively trying to cope with their lucid nightmares. As coping strategies, therapeutic measures were least often taken but were rated as the most helpful. Social interaction and searching the internet were the most used coping strategies but were also considered the least helpful. However, they were mainly perceived as at least somewhat helpful. It is important for future research to work toward a comprehensive model of lucid nightmare etiology to develop effective treatments. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 11.09.2025